Adipic acid [MAK Value Documentation, 2017]. Issue 3 (26th July 2018) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has evaluated adipic acid [124‐04‐9 ] to derive a maximum concentration at the workplace (MAK value), considering all toxicity endpoints. The critical effect is moderate local irritation as shown with the Draize test in the rabbit eye. Available inhalation studies are limited and not suitable to derive a MAK value. Systemic toxicity only occurs at high doses. In a limited oral 2‐year study the body weight of rats was reduced at 2250 mg/kg body weight/day. The resulting systemic NOAEL is 750 mg/kg body weight/day. After comparing adipic acid with other solid acids, a MAK value of 2 mg adipic acid/m 3 I has been set in analogy to phosphoric acid, which is considered to be the worst‐case. As the critical effect is local, adipic acid is assigned to Peak Limitation Category I. In analogy to phosphoric acid, a default excursion factor of 2 is set. Damage to the embryo or foetus is unlikely when the MAK value is observed; thus, the substance is classified in Pregnancy Risk Group C. Adipic acid is not genotoxic and not carcinogenic. No contact sensitizing effects have been observed. Skin contact is not expected to contribute significantly to systemic toxicity. Completed: February 24, 2016